Phytochemical profiling and HPLC quantification of citrus peel from different varieties - Mehmood, Tariq; Khan, Moazzam Rafiq; Shabbir, Muhammad Asim; Zia, Muhammad Anjum (Progress in Nutrition, 2018)
Nutraceutics are well-known for the individuals anxious to attenuate the impact of aging and mitigate the adverse effects of unhealthy lifestyle. Plant-based bioactive compounds are known to offer many health benefits. The objective of this study was to characterize selected phytochemicals and assess antioxidant capacity from citrus processing by-product. Processing waste from different varieties of citrus (oranges, grapefruit and musami) was utilized for the antioxidant indices for extraction with ethanol, methanol and water. The highest antioxidant potential in the form of TPC (206.53±6.82 mg GAE/100 g), flavonoids (83.06±2.74 mg/100 g), DPPH (62.80±2.07 µmole TE/g), ABTS (10.35±0.34 µmole TE/g) and FRAP (18.54±0.61 µmole TE/g) were found in grapefruit ethanolic extract, followed by oranges and musami peel extract. The highest ascorbic acid content (51.3±1.6 mg/100g) was observed in orange peel followed by that in grapefruit and musami peel extracts. On the basis of antioxidant profiling the ethanolic extract of each variety was quantified through HPLC that showed the highest concentration of hesperidin and nobiletin in grape fruit extract as 28.51 and 9.92 mg/g, respectively followed by oranges (24.96 and 7.31 mg/g) and musami (21.38 and 6.08 mg/g) extract.